Development of cow traction technologies and implications for adoption in the East African highlands - Zerbini, E.; Gebre-Wold, A.; Shapiro, Barry I. (International Livestock Research Institute, 1998)
Production performance of cows is an important factor which determines whether cows are adopted for draft power. Working cows could perform at higher levels of efficiency than oxen, but only if nutrient inputs are adequate to meet their greater requirements, and milk production and reproduction are kept at levels comparable to non-working cows. ILRI (International Livestock Research Institute) and the Ethiopian Institute of Agricultural Research (IAR) have reached different aspects of the use of dairy cows for draft work. This paper deals with work output, milk production and reproduction of crossbred dairy cows used for draft. Information generated from ILRI and IAR research is used to elaborate the interplay of factors affecting work output, milk production, metabolism, physiological responses and the reproductive physiology and performance of dairy cows.